Children with myelomeningocele and independence in the toilet activity: A pilot study. (January 2013) - Donlau, Marie; Mattsson, Sven; Glad-Mattsson, Gunilla
Abstract Objective: Regarding adult life and independence the most common obstacles for young adults with myelomeningocele (MMC) are cognitive dysfunction and difficulties in performing toilet activities. A step-by-step method with goal setting for the training of self-care in toilet activities for children with MMC was evaluated. Method: Twenty-two children with MMC and bladder and bowel dysfunction (12 girls, 10 boys) aged 3–17.2 (m 9.1) were included. The toilet activities were observed at home jointly by an occupational therapist and urotherapist. Goal-setting procedures of self-training were promoted. Observation scores before and after intervention were compared, the goal setting being evaluated on a Goal Attainment Scale (GAS). Results: Fifteen children who trained in self-catheterization had a median observation score of 22 before and 37 after the training period (p = 0.002). Another seven trained in trans-rectal irrigation with a median score of 30 before and 49 after (p = 0.02). As a result of GAS all children improved, of whom 17 reached the goal or even more so than expected. Conclusions: In this pilot study mutual goal setting in a step-by-step training programme based on professional observation of the toilet activity at home showed a better outcome than traditionally performed training in a hospital setting or with traditional habilitation support.